Conventional pricing 1 - Coussins, Ricky (Henry Stewart Talks, 2010)
Pricing decisions, Price is key, Marketing leads price, Important pricing concepts, Break even analysis, Elasticity of demand, Ten conventional pricing models and how to apply them, Cost based, Historic pricing, Competitive driven, Target return, Target ROI, Range, Segment based, Skimming, Guess, Apparent value